In situ visualization of zinc plating in gel polymer electrolyte. (20th September 2021) - Jeon, Yuju; Wu, Yutong; Zhang, Yamin; Hwang, Chihyun; Lee, Hyun-Wook; Song, Hyun-Kon; Liu, Nian
Abstract: Uniform zinc metal plating has been raised as a critical issue in zinc-based batteries. Randomly localized ions lead to severe zinc dendrite formation in liquid electrolyte due to nonuniform ion flux caused by electroconvective flow. One of the mitigating approaches is to use gel polymer electrolyte to regulate the ion flux for suppressing zinc dendrites by imparting viscoelasticity to the electrolyte and improving the ion transport along charged functional groups of polymer chains. However, to this date, the effectiveness of gel polymer electrolyte has been visualized using ex situ methods (e.g., scanning electron microscopy) that requires cell disassembly. And the underlying mechanism is poorly understood. Herein, we applied in situ optical microscopy with dark-field illumination and a transparent glass slide cell to visualize zinc metal plating in the gel polymer electrolyte. At a given current density, the morphological differences of plated zinc metal between the liquid and gel polymer electrolytes were compared. Our in situ optical microscopy platform successfully showed that the gel polymer electrolyte supported by cross-linked polyacrylic acid (PAA)/N, N'-methylenebisacrylamide (MBA) polymer framework significantly suppressed the dendrite formation in contrast to the liquid electrolyte during plating. In addition, at various current densities, the tendency of dendritic growth was observed and statistically compared in both electrolytes. The findings will be useful for future design of rechargeable zinc-based batteries.